Ecossistema bibliográfico: orientações para sustentabilidade na catalogação - Caruzzo, Marina Bortolotti Biudes (Universidade Federal de São Carlos, 2024)
Cataloging finds in Information and Communication Technologies ways to enhance and modernize its practices, products, and services. Bibliographic data comes to be analyzed individually, while metadata structures them and are crucial for describing, organizing, identifying, and incorporating them into different environments. With this configuration, forms of cooperation and reuse of bibliographic data stand out, that is, actions that can contribute to sustainability by minimizing the excess production and lack of control of this data. The objective is to establish a sustainable proposal for cataloging, in the use and economy of bibliographic data. For this purpose, domain analysis was chosen as the method, which made it possible to verify the elements that compose the current bibliographic ecosystem and identify technological trends, collective patterns, and relationships that can contribute to the sustainability of bibliographic data. As a result, guidelines for sustainable cataloging are proposed, which were possible after reflecting on the elements of cataloging that contribute to the better use of bibliographic data, and curation is discussed as a process included in cataloging. Furthermore, it was possible to point out how the improvement of the bibliographic ecosystem can contribute to the Sustainable Development Goals of the 2030 Agenda, especially SDGs 4, 8, 11, 12, and 16, highlighted in the final considerations.
Bibliographic ecosystem: guidelines for sustainability in cataloging
Keywords: Dados bibliográficos; Sustentabilidade; Cooperação; Reuso; Ecossistema bibliográfico; Cooperation; Bibliographic data; Sustainability; Reuse; Bibliographic ecosystem; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO